(±)‐cis‐4a‐alkyl‐1, 3, 4, 4a, 9, 9a‐hexahydro‐2H‐carbazol‐2‐ones by domino nitro reduction‐aza‐Michael addition to enones. (6th January 2022) - Embrey, Samuel J.; Barrios‐Perez, Carlos; Bunce, Richard A.
Abstract: A domino nitro reduction‐aza‐Michael addition sequence has been investigated for α, β‐unsaturated ketones and compared with the analogous reaction for conjugated esters. As expected, six‐membered ring closures of ketones did not proceed as well as for esters (<60% vs. >85%) due to the greater inherent reactivity of the ketones. This problem was minimized by performing the cyclization at lower temperature for a shorter time. The process has been extended to a synthesis of (±)‐ cis ‐4a‐alkyl‐1, 3, 4, 4a, 9, 9a‐hexahydro‐2 H ‐carbazol‐2‐ones with good yields (65%–86%). While the rigidity of the system and closure of the smaller five‐membered ring created some strain in the products, yields were acceptable. The cis ring junction resulted from axial attack to give a more stable chair‐like enol that tautomerized to the target heterocycle. Abstract :